The development of vocabulary and reading comprehension among Icelandic second language learners - Sigríður Ólafsdóttir 1958- (2015)
The purpose of this study was to explore the development of vocabulary and reading comprehension among Icelandic second language learners (Ice2), the relation between these skills and to examine the extent to which linguistic and contextual factors might influence their emergence. Two age groups of Ice2 learners were tested at three time points; the younger group (49 children) in grades four, five, and six, and the older group (41 children) in grades six, seven, and eight. A comparison group of age peers with Icelandic as their first language (Ice1; 41 children in the younger group and 55 in the older group) was tested concomitantly. The Ice2 children had lower vocabulary scores than the Ice1 children in grade four and the gap between the two groups widened during the study period. The Ice1 learners’ superior vocabulary skills were also reflected in their greater use of higher order, academic words. For both groups, the number of these words went up in line with an increased ability to express their ideas in print in support of their arguments. While both the Ice2 and the Ice1 children made an unstable improvement in reading comprehension, the gap between the two groups remained the same. Icelandic word skills in fourth grade positively predicted the rate of growth in reading comprehension for both the Ice2 and the Ice1 children. This means that those who started with better word skills increased their reading comprehension scores at a faster rate than those who started with poorer vocabulary. The older the Ice2 learners were when they arrived in Iceland the faster they increased their vocabulary and reading comprehension scores. A difference emerged in each grade between the vocabulary and the reading comprehension skills of Ice2 learners with European first languages and their Ice2 peers with non-European first languages, always in favour of the former. First language proficiency and literacy, as estimated by parents, first language instruction, and maternal education did not influence initial vocabulary and ...